Tradition of the Mandondon Agreement In the South Tapanuli Community as Seen from the Face of Islamic Law - M. Kamil Siregar (AT-TAFAHUM: Journal of Law, 2018)
Tradition of Mandondon contract is a people's habit in Sipirok sub-district, the south Tapanuli in getting loan (debit) by pawning their rice field to the capital owner, but it will become a guarantee and will be controlled by people receiving pawning, and they may cultivate to utilize it, then collects the results of the rice field during debit must be returned by mortgaging with the same amount, so that people who are pawning to be lost. The main problems in this research, (1) how are the essence and the implementation of Mandondon contract in Sipirok sub-district? (2) How are the reviews of Islamic law to tradition of Mandondon contract in Sipirok sub-district?. Then, the general goals achieved in this research are to know the essence and the implementation of the Mandondon contract. The particular goal is to know how the review of Islamic law to tradition of Mandondon contract. This research is a field research using data analysis method, a qualitative method, using a case approach. The data source of this research is people pawning their rice field, the person receiving the pawn, adat's figure, and MUI chairman. The results of this research show that practice agreement of Mandondon contract (pawn rice field) if it is seen in qualified term, it is already qualified, but has not fulfilled the principle becausein thepawnshop is not yet clear the deadline for repayment of debt which must be done by the mortgage to the recipient of the pledge, then in the implementation that occurs in the Sipirok's community are not perfect pawnshops or not according to Islamic shari'a. In pawn practices, researchers find that there are elements of usury and utilization of the mortgaged goods.